2017
DOI: 10.1002/jcph.974
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of a Single Oral Dose of Mirogabalin in Japanese Subjects With Varying Degrees of Renal Impairment

Abstract: Mirogabalin (DS‐5565) is a novel preferentially selective α2δ‐1 ligand being developed for the treatment of diabetic peripheral neuropathic pain and postherpetic neuralgia. The current multicenter open‐label study determined the effect of varying degrees of renal impairment on the pharmacokinetics and safety of a single dose of mirogabalin 5 mg in Japanese subjects. A total of 30 subjects (6 subjects per renal function category [normal, mild, moderate, or severe impairment; and end‐stage renal disease (ESRD)])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…a drug that only affects renal clearance (cimetidine). The increase in mirogabalin exposure with cimetidine is similar to the increase observed in patients with mild renal impairment, for whom mirogabalin dose adjustments are not considered necessary 22. Additionally, since the effect of probenecid on mirogabalin is not significant (>2‐fold), mirogabalin dose adjustments may not be necessary with concomitant probenecid.…”
Section: Resultsmentioning
confidence: 53%
“…a drug that only affects renal clearance (cimetidine). The increase in mirogabalin exposure with cimetidine is similar to the increase observed in patients with mild renal impairment, for whom mirogabalin dose adjustments are not considered necessary 22. Additionally, since the effect of probenecid on mirogabalin is not significant (>2‐fold), mirogabalin dose adjustments may not be necessary with concomitant probenecid.…”
Section: Resultsmentioning
confidence: 53%
“…Mirogabalin is rapidly absorbed, and elimination occurs mainly via renal excretion (61% to 72%) . Owing to its renal elimination, a reduction in the dose of mirogabalin is recommended for patients with moderate or severe renal impairment . Following oral administration of doses ranging from 3 to 75 mg in healthy volunteers, the peak and total exposure to mirogabalin increases proportionally with increasing doses .…”
mentioning
confidence: 99%
“…6,7 Owing to its renal elimination, a reduction in the dose of mirogabalin is recommended for patients with moderate or severe renal impairment. 8,9 Following oral administration of doses ranging from 3 to 75 mg in healthy volunteers, the peak and total exposure to mirogabalin increases proportionally with increasing doses. 6 The time of peak plasma concentration of mirogabalin is 1 hour with a mean half-life ranging from 3.0 to 4.9 hours.…”
mentioning
confidence: 99%
“…A predominantly renal route of elimination and minimal metabolism of mirogabalin was reported in animal studies . Due to its renal elimination, a dose reduction of mirogabalin is recommended for patients with moderate or severe renal impairment …”
mentioning
confidence: 98%
“…16 Due to its renal elimination, a dose reduction of mirogabalin is recommended for patients with moderate or severe renal impairment. 17,18 In clinical studies, mirogabalin demonstrated promising results in patients with diabetic peripheral neuropathy. A phase 2 study in 452 patients with diabetic peripheral neuropathic pain reported that mirogabalin doses from 15 to 30 mg/day were the most effective and significantly reduced average daily pain scores compared with placebo.…”
mentioning
confidence: 99%